Calcium Silicate Recommendations for Sugarcane on Florida Organic Soils - J. Mabry McCray; Ronald W. Rice; Leslie E. Baucum (EDIS)
Although silicon isn’t an essential plant nutrient, adding calcium silicate to soils low in soluble silicon increases yield an average of 20%. This 5-page fact sheet describes calcium silicate recommendations for sugarcane on organic soils, developed using field studies at several locations. Written by J. Mabry McCray, Ronald W. Rice, and Leslie E. Baucum, and published by the UF Department of Agronomy, August 2011. (UF/IFAS Photo: Josh Wickham)